Characteristics of Tight Dolostone Reservoir and Its Main Controlling Factors in the Submember Ma55 of Majiagou Formation in the Western Ordos Basin. (20th April 2023) - Li, Baiqiang; Zhou, Taofa; Wu, Zhenzhen; Ketchaya, Yanick Blaise; Wang, Qicong; Zhang, Xiaoli; Du, Jiangmin; Quaye, Jonathan Atuquaye
Abstract : The tight carbonate reservoir was controlled by various geological factors, and such factors played different roles in buried depths and formations. Therefore, studies related to the factors controlling carbonate reservoir distribution are of great significance for the prediction and evaluation of high-quality dolostone reservoirs. In this paper, we focus on the controlling factor of the submember Ma55 dolostone reservoir in the western Ordos Basin. The main rock types, reservoir pores, physical properties, and pore structure characteristics of the reservoir were analyzed by thin section identification, physical property analysis, and mercury injection, respectively. Then, the main controlling factors of reservoir development were comprehensively analyzed from the perspectives of palaeostructure, lithofacies palaeogeography, diagenesis, and diagenetic facies. The results show that two kinds of dolostone reservoirs in the submember Ma55 developed in the western Ordos Basin, including intercrystalline pore-type and dissolution pore-type. The former reservoir is primarily characterized by powder-fine dolostone with residual structure, dolomite intercrystalline pore, and micropore with porosity ranging from 2% to 11%. There are three types of pore structures developed in it, such as macropore-medium throat-single peak (MAMS), macropore-fine throat-single peak (MAFS), and medium pore-fine throat-single peak (MEFS). The latter reservoir is mainly featured by powdery crystalline dolostone with gypsum and halite dissolution, moldic pore, and dissolved pore between breccias with a porosity greater than 5%. It consists of two types of pore structures, such as macropore-fine throat-single peak (MAFS) and medium pore-coarse throat-multipeak (MECM). The intercrystalline pore-type dolostone reservoir is mainly controlled by the lithofacies palaeogeographic environment and diagenesis. In specific, the shoal microfacies at the edge of the platform and the active reflux seepage dolomitization are the basic sedimentary environment conditions for reservoir formation and the key to reservoir formation, respectively. The dissolution pore-type dolostone reservoir is primarily influenced by both paleostructure and diagenesis. The relatively high part of the paleostructure provides favorable conditions for the formation of evaporate minerals, and early freshwater dissolution is the key to reservoir formation. This research will provide a theoretical basis for forecasting the favorable distribution areas of different types of dolostone reservoirs.